Forecasting Annual UK Inflation using an Econometric Model over 1875–1991. - Clements, M; Hendry, D (Emerald Group Publishing Limited, 2008)
In recent work, we have developed a theory of economic forecasting for empirical econometric models when there are structural breaks. This research shows that wellspecified models may forecast poorly, whereas it is possible to design forecasting devices more immune to the effects of breaks. In this chapter, we summarize key aspects of that theory, describe the models and data, then provide an empirical illustration of some of these developments when the goal is to generate sequences of inflation forecasts over a long historical period, starting with the model of annual inflation in the UK over 1875– 1991 in Hendry (2001b).